Cerebral-cardiac embolism. Cerebrovascular-cardiac embolic stroke. - Henriques, I (Acta Médica Portuguesa, 1997)
The diagnosis of cerebral cardioembolism requires, apart from evidence of an embolic cardiopathy, a cause-effect relation to be established between the potential cardioembolic source and the occurrence of ischemic stroke. There are several arguments in favour of this reaction, namely the neurologic aspects put forward both clinicians and neuroimaging professionals, as well as the generalization of cardiologic diagnostic techniques for the etiologic investigation of ischemic stroke. Importance should be given to primary prevention of embolic cardiopathies. Oral anticoagulation should be administered in all situations where an advantage has been established when compared to antiaggregation or placebo. Cooperation between the different health structures and the different specialties probably depends on the changes in the prevalence of cerebral cardioembolism.